Genetic dissection of top three leaf traits in rice using progenies from a japonica × indica cross. Issue 12 (7th November 2017) - Yin, Changbin; Li, Huihui; Zhao, Zhigang; Wang, Zhiquan; Liu, Shijia; Chen, Liangming; Liu, Xi; Tian, Yunlu; Ma, Juan; Xu, Lidong; Zhang, Dashuang; Zhu, Susong; et al.
Abstract: The size of the top three leaves of rice plants is strongly associated with yield; thus, it is important to consider quantitative traits representing leaf size (e.g., length and width) when breeding novel rice varieties. It is challenging to measure such traits on a large scale in the field, and little is known about the genetic factors that determine the size of the top three leaves. In the present study, a population of recombinant inbred lines (RILs) and reciprocal single chromosomal segment substitution lines (SSSLs) derived from the progeny of a japonica Asominori  × indica IR24 cross were grown under four diverse environmental conditions. Six morphological traits associated with leaf size were measured, namely length and flag leaf, length and flag, second and third leaves. In the RIL population, 49 QTLs were identified that clustered in 30 genomic region. Twenty‐three of these QTLs were confirmed in the SSSL population. A comparison with previously reported genes/QTLs revealed eight novel genomic regions that contained uncharacterized ORFs associated with leaf size. The QTLs identified in this study can be used for marker‐assisted breeding and for fine mapping of novel genetic elements controlling leaf size in rice. Abstract : Top three leaves in rice determine plant type and grain yield. Using one japonica×indica cross, we identified 30 genomic regions and then confirmed 23 of them affecting length and width of the top three leaves. Compared with length, width is more correlated with each other, sharing more common genes.